Jurnal Sistem Informasi Geografis Jumlah Kendaraan Provinsi Jawa Tengah 2019-2021 - Farhan Afrian; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Geographic Information System (GIS) is a computer information system used to process and store spatial data or information. The aim of this research is to produce a geographic information system that maps the number of vehicles in Central Java Province from 2019 to 2021. The method used in this research involves collecting vehicle census data from related sources such as Central Java Province. . Central Statistics Agency (BPS) and spatial data as well as the number of vehicles from 2019 to 2021 in Regencies or Cities in Central Java Province. Digitalization of Mapping using Quantum GIS software. The results of this research are expected to provide a better understanding of vehicle distribution and volume trends vehicles in Central Java Province from 2019 to 2021. This information can be used for various purposes such as traffic planning, infrastructure development and reducing traffic congestion. The geographic information system that maps the number of vehicles in Central Java Province is expected to provide significant benefits for the government, researchers and the general public to make better decisions regarding traffic and traffic problems in the region.